Influence of Nutrient Contents and Particle Sizes on the Functional Characteristics of Moringa oleifera Leaf (Lam) Powders - Armel, Assiéné Agamou Julien; Serge, Assiéné Oyong Damase; Esther, Ngah (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
Background: The Moringa oleifera is a tree native to Asia and widely cultivated in sub-Saharan Africa and all Cameroon regions. Their nutritional and medicinal potential has recently appealed to the attention of various researchers and industries worldwide. Objective: This study aims to determine the influence of the contents of compounds and particle size on the functional properties of leaf powders of M. oleifera. Methodology: The leaves were collected from three farms in the localities of Mbouda and Maroua and processed in powders. The M. oleifera leaf powders were analyzed for moisture, protein, lipid, and ash contents. The proximate composition, some functional properties such as particle size, true Water Absorption Capacity (WACt), apparent Water Absorption Capacity (WACa), Water Solubility Index (WSI), Oil Holding Capacity (OHC), and Bulk density were determined. Stat-graphic Centurion 15.2 software (StatPoint Technologies, Inc, Warrenton, Virginia, USA) was used for statistical analysis. Results: The mean contents of young and mature leaves powders are 24.96 ± 0.29 and 23.13 ± 0.50 g/100 DM in total proteins; 34.26 ± 0.52 and 29.11 ± 1.44 g/100g DM in available carbohydrate, 8.34 ± 0.64 and 8.34 ± 0.68 g/100g DM in total lipids, 8.75 ± 0.74 and 9.08 ± 0.48 g/100g DM in total ash, 21.13 ± 1.34 and 27.14 ± 1.04 g/100g DM in total fibers, respectively. The particle size of young and mature leaf powders of M. oleifera varies from 40 to 800 µm. The particle size of powders is majority large. The fiber's contents significantly affect the increase of rehydration properties and the OHC, while the large particle size, the density. Values of WACt and WACa are 27.02 ± 0.20 and 32.88 ± 1.24 % in young leaves and 28.98 ± 0.15 and 35.88 ± 1.02 % in mature leaves, respectively. The WSI and OHC are 3.02 ± 0.06 and 257 ± 1% in young leaves and 3.5 ± 0.04 and 261 ± 2 % in mature leaves, respectively. The Bulk density is 0.42 ± 0.01 g/ml in young leaves and 0.39 ± 0.01 in mature leaves. Conclusion: Functional properties of M. oleifera leaf powders do not always depend on the contents of compounds and particle size distribution. To maximize these properties, fiber contents and the more abundant particle size should be considered.